(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Acute otitis media (AOM) continues to be a common infection in young children. Milder disease, usually due to viruses or less virulent bacteria, resolves equally quickly with or without antibiotics. A bulging tympanic membrane, especially if yellow or hemorrhagic, has a high sensitivity for AOM that is likely to be bacterial in origin and is a major diagnostic criterion for AOM.Perforation of the tympanic membrane with purulent discharge similarly indicates a bacterial cause. Immediate antibiotic treatment is recommended for children who are highly febrile (≥39°C), moderately to severely systemically ill or who have very severe otalgia, or have already been significantly ill for 48 h. For all other cases, parents can be provided with a prescription for antibiotics to fill if the child does not improve in 48 h or the child can be reassessed if this occurs. Amoxicillin remains the clear drug of choice. Ten days of therapy is appropriate for children <2 years of age, whereas older children can be treated for five days.